Improving Access to Justice in E-commerce: The Potential of Online Dispute Resolution (ODR) - Muryanto Lanontji; Wahyudi Umar; wahyuni, ayu (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to analyze the potential of Online Dispute Resolution (ODR) in increasing access to justice in E-commerce with a normative legal approach. This research method is carried out through an in-depth literature analysis on the concept of ODR, comparison with conventional dispute resolution, and case studies of ODR implementation in the context of E-commerce. In the literature analysis, legal norms related to ODR, consumer rights, and data protection aspects are analyzed to understand the existing regulatory framework. The study also compares the advantages and disadvantages of ODR compared to traditional dispute resolution mechanisms, with reference to the principles of fairness, efficiency, and accessibility. In addition, this method involves analyzing ODR implementation case studies in leading E-commerce platforms. This study also conducted interviews with digital law experts to get views on legal aspects that need to be considered in the implementation of ODR. The results of this study outline the potential of ODR in facilitating easier and more efficient access to justice for consumers in E-commerce disputes. However, data protection norms and ODR regulations need to be strengthened to maintain privacy and security. The implications of this study will provide valuable legal guidance for policymakers, lawyers, and E-commerce platforms in integrating ODR effectively, while maintaining normative and ethical aspects in dispute resolution in an ever-evolving digital world.